Congenital generalized lipodystrophy in children: Berardinelli-Seip syndrome - two rare cases with renal manifestations - S Satya; Gandikota Raghu Rama Rao; K Prathima; D Lavanya; K Sandeep; A Amareswar (Wolters Kluwer Medknow Publications, 2017)
Berardinelli-Seip syndrome is a rare autosomal recessive disorder characterized by an almost total lack of subcutaneous fat with various metabolic abnormalities and complications such as diabetes mellitus and insulin resistance. Renal changes and complications are uncommon but reported. We present two such rare cases with renal involvement.